Detection of interstitial pneumonia with autoimmune features and idiopathic pulmonary fibrosis are enhanced by involvement of matrix metalloproteinases levels and clinical diagnosis. Issue 11 (17th October 2022) - Liu, Mingtao; Xue, Mingshan; Zhang, Teng; Lin, Runpei; Guo, Baojun; Chen, Youpeng; Cheng, Zhangkai J.; Sun, Baoqing
Abstract: Background: Higher detection of interstitial pneumonia with autoimmune features (IPAF), and idiopathic pulmonary fibrosis (IPF), has significant diagnostic and therapeutic implications. Some matrix metalloproteinases (MMPs) have become reliable diagnostic biomarkers in IPAF and IPF in previous studies, yet relevant reliability remains to be recognized. Materials and Methods: In this study, 36 ILDs patients, including 31 IPAF patients (Mean ± SD, 50.20 ± 5.10 years; 16 [51.6%] females) and five IPF patients (Mean ± SD, 61.20 ± 6.73 years; one [20.0%] females) were retrospectively enrolled. Serial serum samples were collected from patients with IPAF and IPF between January 2019 and December 2020. Notably, Serum MMPs levels were measured by U‐PLEX Biomarker Group 1(Human) Multiplex Assays (MSD, USA). Results: A combination of MMPs and combinatorial biomarkers was strongly associated with clinical subjects in this study (AUC, 0.597 for Stability vs. Improvement and 0.756 for Stability vs. Exacerbation). Importantly, the AUC of MMP‐12 reaches 0.730 ( p < 0.05, Stability AUC vs. Improvement AUC) while MMP‐13 reaches 0.741 ( p < 0.05, Stability AUC vs. Exacerbation AUC) showed better performance than other MMPs in two comparisons. Conclusions: Clinical risk factors and MMPs are strongly associated with either stratification of the disease of progression of IPAF or in two IPAF and IPF independent cohorts. To our knowledge, this is the first to illustrate that MMP‐12 and MMP‐13 may be expected to become typical promising biomarkers in Improvement – IPAF and Exacerbation – IPAF, respectively. Abstract : Serum levels for each severity stratification of IPAF were in the selected MMPs, while MMP‐12 and MMP‐13 have significance in Improvement‐IPAF and Exacerbation‐IPAF, respectively.